2011
DOI: 10.1016/j.kjms.2011.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between remaining teeth and self‐rated chewing ability among population aged 45 years or older in Kaohsiung City, Taiwan

Abstract: The purposes of this study were to (1) examine the relationship between the number of various types of healthy remaining natural teeth at different sites and self-rated chewing ability and (2) evaluate the relationship between the number of functional tooth units (FTUs), comprising functional natural teeth (FNT) or fixed prostheses, and self-rated chewing ability. A sample of 296 adults (122 men and 174 women), aged 45 years or older (average age, 56.6±9.7), were recruited from seven dental clinics in Kaohsiun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 40 publications
4
35
0
2
Order By: Relevance
“…Worse, no news about serious federal preventive dental policy to change this scenario and, as we observed in this study, patients as young as 40 years, still suffer with loss of teeth with consequent chew's disability and impairment of quality of life, similar to what was found by Silva et al [10]. A study conducted in Taiwan by Hsu et al [7] observed as well that the increase of age also increase the number of tooth loss. That study concluded that the number of healthy remaining teeth, including natural teeth and fixed prostheses are key factors in chewing ability.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Worse, no news about serious federal preventive dental policy to change this scenario and, as we observed in this study, patients as young as 40 years, still suffer with loss of teeth with consequent chew's disability and impairment of quality of life, similar to what was found by Silva et al [10]. A study conducted in Taiwan by Hsu et al [7] observed as well that the increase of age also increase the number of tooth loss. That study concluded that the number of healthy remaining teeth, including natural teeth and fixed prostheses are key factors in chewing ability.…”
Section: Discussionsupporting
confidence: 86%
“…Studies have indicated that the decrease of number of teeth and for complete denture wearers the chew's ability is significantly less efficient and this may have consequences over general health and QoL of those patients. The negative impact on oral healthrelated quality of life (OHRQoL) may also be due to poor speech, pain, and dissatisfaction with appearance [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that having fewer than 20 teeth is related to inadequate dental function and impaired masticatory ability 32 34 35. In contrast, having a ‘functional dentition’ (more than 20 natural teeth) has associations with chewing ability,36 and consumption of fruits and vegetables 37. There is also evidence of an association between tooth loss and OHRQoL, both among adults in general and also among older adults 38 39.…”
Section: Methodsmentioning
confidence: 99%
“…The negative impact on oral health-related quality of life (OHRQoL) may also be due to poor speech, pain, and dissatisfaction with appearance. [47]…”
Section: Introductionmentioning
confidence: 99%